Tolerance and safety of rapid 2-hour infusion of rituximab in patients with kidney-affecting autoimmune diseases and glomerulonephritides: a single-centre experience. Issue 4 (28th February 2018) - Hartinger, Jan Miroslav; Satrapová, Veronika; Hrušková, Zdenka; Tesař, Vladimír
Abstract : Objective: According to the manufacturer's documentation, rituximab (RTX) should be administered with slow infusion rates to prevent infusion-related adverse events (AEs). Nevertheless, slow infusions are time-consuming and uncomfortable for patients and medical staff. Therefore, faster infusion rates have been studied and proven safe and well tolerated in lymphomas and rheumatoid arthritis (RA). A small amount of data is available for rapid RTX infusions in non-RA autoimmune diseases. Methods: Beginning in September 2015, all RTX-reated patients in our centre and willing to participate, were switched from slow RTX infusions (4.25 hours, given at least once to all patients) to fast infusions (2 hours). A total of 85 RTX 2-hour infusions was administered to 53 patients with autoimmune diseases with renal involvement and selected primary glomerulonephritides (26 ANCA-associated vasculitis, nine systemic lupus erythematodes, seven membranous nephropathy, five IgM nephropathy and six other autoimmune disease). Most of the patients received chronic corticosteroid therapy. The prednisone equivalent dose median (IQR) was 0.1 (0.0–0.2) mg/kg/day. Results: Rapid RTX infusions were generally well tolerated. Only two infusion-related AEs were recorded: one Common Terminology Criteria for Adverse Events, grade 3, (lower back pain and hypotension followed by chills necessitating methylprednisolone and dipyrone administration) and one grade 1 (subjective intolerance). The AEs frequency does not differ from other studies with rapid RTX infusions in patients with lymphomas and RA. Conclusions: Our experience supported other published data and provides evidence concerning the safety of non-initial RTX 2-hour infusion which can be administered without raising the infusion-related AEs rate in patients with kidney-affecting autoimmune diseases and glomerulonephritides.